Implementasi Corporate Social Responsibility melalui Pemberdayaan Masyarakat Desa Sungai Kupah - Suzana, Fenny Rema; Heniwati, Elok (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2026)
Research aims: This study aims to analyze the application of Stakeholder Theory in implementing PT Pertamina Patra Niaga DPPU Supadio's Corporate Social Responsibility (CSR) program in Sungai Kupah Village, Sungai Kakap District, Kubu Raya Regency. The research is motivated by the importance of involving various stakeholders in implementing a sustainable CSR program and delivering real benefits to the community. Design/Methodology/Approach: The approach used is a qualitative case study method. Data were collected through in-depth interviews, field observations, and document analysis. Research informants Data analysis was carried out using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data presentation, and drawing conclusions. Research findings: The research results show that Pertamina's CSR implementation has applied the principles of Stakeholder Theory through appropriate stakeholder identification, active stakeholder involvement in program implementation, and ongoing collaboration between the company, village government, and the community. The CSR program generates economic, social, and environmental benefits while supporting sustainable village development. Theoretical contribution/Originality: The theoretical contribution of this research lies in enriching the literature on the application of Stakeholder Theory to community empowerment-based CSR and the management of local potential in coastal areas. Practitioner/Policy implication: Practically, the research findings demonstrate the importance of a participatory and collaborative approach in CSR program design to increase program effectiveness, acceptability, and sustainability. The research findings also provide policy implications for companies and local governments in strengthening multi-stakeholder partnerships to support sustainable village development.